Relationship between pyroptosis-mediated inflammation and the pathogenesis of prostate disease - Zhao, Ming; Guo, Jun; Gao, Qing-He; Wang, Hao; Wang, Fu; Wang, Zi-Rui; Liu, Sheng-Jing; Deng, Ying-Jun; Zhao, Zi-Wei; Zhang, Yue-Yang; Yu, Wen-Xiao (Frontiers in Medicine, 2023)
The largest solid organ of the male genitalia, the prostate gland, is comprised of a variety of cells such as prostate epithelial cells, smooth muscle cells, fibroblasts, and endothelial cells. Prostate diseases, especially prostate cancer and prostatitis, are often accompanied by acute/chronic inflammatory responses or even cell death. Pyroptosis, a cell death distinct from necrosis and apoptosis, which mediate inflammation may be closely associated with the development of prostate disease. Pyroptosis is characterized by inflammasome activation via pattern recognition receptors (PRR) upon recognition of external stimuli, which is manifested downstream by translocation of gasdermin (GSDM) protein to the membrane to form pores and release of inflammatory factors interleukin (IL)-1β and IL-18, a process that is Caspase-dependent. Over the past number of years, many studies have investigated the role of inflammation in prostate disease and have suggested that pyroptosis may be an important driver. Understanding the precise mechanism is of major consequence for the development of targeted therapeutic strategies. This review summarizes the molecular mechanisms, regulation, and cellular effects of pyroptosis briefly and then discuss the current pyroptosis studies in prostate disease research and the inspiration for us.